Contribution of genes related to grain number (Gn1a and WFP) introgressed into NERICA 1 to grain yield under tropical highland conditions in central Kenya - Kikuta, Mayumi; Menge, Daniel Makori; Gichuhi, Emily Waringa; Samejima, Hiroaki; Tomita, Rena; Kimani, John Munji; Musila, Ruth Nzisa; Doi, Kazuyuki; Ashikari, Motoyuki; Angeles-Shim, Rosalyn; Jena, Kshirod Kumar; Makihara, Daigo (Informa UK Limited, 2023)
In Kenya and many other African countries, improving rice productivity is vital for future food security. To improve rice productivity in Kenya, near-isogenic lines (NIL) were developed by introducing Gn1a and WFP, genes that function to increase grain number per panicle by increasing secondary and primary rachis-branches, into NERICA 1, a registered variety in Kenya. The aim of this study was to determine whether the introduction of these genes has the potential to improve rice productivity under tropical highland conditions in central Kenya. Field experiments were conducted in 2016 and 2017 at a lowland rice field in Mwea, Kenya, under different nitrogen fertilization conditions using three lines of NERICA 1 introgressed with Gn1a and/or WFP (NIL-Gn1a, NIL-WFP, and NIL-Gn1a+WFP) and their recurrent parents, NERICA 1. Two years of field experiments revealed that the introgression lines enhanced grain yield by increasing the number of primary and secondary rachis-branches and the number of grains per panicle. Gn1a and WFP showed additive effects and the introgression of both genes alleviated the negative effects on yield components observed in the introgressed lines, resulting in higher grain yield. Sufficient nitrogen fertilization was required to increase yield in the single-gene introgression lines. However, the line with both Gn1a and WFP achieved reasonable yields even under low fertilizer conditions in Mwea, Kenya. As these introgression lines have similar growing characteristics to their parent variety, they are expected to contribute to increased rice production in Kenya and similar environments in sub-Saharan Africa.